Karakteristik Fisikokimia dan Sensori Kopi Cold Brew Kamojang Berdasarkan Proses Pasca Panen - Febrianto Ilham Santoso; Novian Wely Asmoro; Retno Widyastuti (Universitas Mercu Buana Yogyakarta, 2025)
Coffee is a beverage derived from the beans of the coffee plant that have been processed and then brewed. The post-harvest process of coffee beans includes sorting, fermentation, drying, roasting, grinding and brewing. Fermentation can be dry (natural, honey) or wet (full wash, semi-wash), while brewing can be hot or cold. Kamojang coffee is grown in the highlands of Mount Kamojang, West Java. The coffee used was Kamojang Arabica coffee with natural, honey and wash post-harvest methods, roasted at 170°C for 15 minutes, medium roast darkness and ground to medium size then brewed with Cold brew. This study used different post-harvest methods, with testing parameters of pH, caffeine and organoleptic. The Cold brew method starts with grinding coffee powder, then mixing it with water at room temperature and then storing it at room temperature for 10 hours. The organoleptic tests were performed by 30 untrained panelists with the test parameters of taste, aftertaste, sweetness, bitterness, acidity and overall. Statistical tests were then performed using ANOVA and DMRT tests. Kamojang Cold brew has a caffeine concentration of 305.49 - 310.08 mg/L. Kamojang Cold brew has an average pH of 5.3 - 5.7. In the organoleptic test, on a scale of 1 to 5, the average flavor, bitterness, sweetness, acidity, aftertaste, and overall taste ranged from 2.8 to 4.